STUDI ETNOBOTANI TUMBUHAN OBAT YANG DIMANFAATKAN OLEH MASYARAKAT DI KECAMATAN SINDANG KELINGI KABUPATEN REJANG LEBONG BENGKULU - Kasrina Kasrina; Veriana Veriana (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract-This study aims to document the medical plants and their use for tradisional healing by people the people in Kelingi Rejang Lebong Bengkulu. A research has conducted in Januari-Maret 2014 using observation and purpose interview methods. Herbarium specimens has collected and determined. Result study documented 117 specieses from 53 families af plants were reported to be used by them as medicines for 78 diseases. Diseases such stomached, hypertention, cancer, defacate trouble, ulcerous, fertility, etc. Furthermore, a kind of plant such as Temu lawak (Curcuma xanthorizha/Zingiberaceae) is able to heal more then one diseases. Leaves are the most part of plant used for healing. Followed by fruit and stem. Dominance the medical plant put on gardens (62%) Keywords: ethnobotanical, traditional medicine, medical plant, bengkulu